Investigation of liquefaction and pore water pressure development in layered sands - Ozener, Pelin Tohumcu; Ozaydin, Kutay; Berilgen, Mehmet M. (SPRINGER, 2009)
This paper presents the results of shaking table model tests which were carried out to investigate the pore water pressure generation and related liquefaction mechanism in layered sand deposits. The experiments were performed on uniform sand columns, silt interlayered sand columns and two layered sand columns deposited at various relative densities and subjected to different input excitations. During the experiments excess pore water pressures were measured by pore pressure transducers installed at three different depths and, surface settlements and thickness of water film developed under less permeable inclusions were measured by a digital camera. The experimental results are discussed and compared to demonstrate the effects of relative density, input acceleration and presence of a silt seam on the generation of excess pore water pressure in sand deposits subjected to dynamic loading. The results showed that the presence of a less permeable silt interlayer within the sand deposit and existence of a loose sand layer underlying dense sand deposits can have significant effect on the pore water pressure generation mechanism.
Keywords: Liquefaction; Layered sand; Water film; Model tests; Silt interlayer; MECHANISM; FILM; Engineering; Geology